Converting industrial waste cork to biochar as Cu (II) adsorbent via slow pyrolysis. (15th March 2020) - Wang, Qihang; Lai, Zongyuan; Mu, Jun; Chu, Demiao; Zang, Xiaorong
Graphical abstract: Highlights: Providing a simple and reliable method for utilize industrial waste cork. Relations between pyrolysis conditions and biochar characteristics were revealed. The specific surface area of cork biochar (392.5 m 2 /g) surpasses most biochars. Cork biochar exhibits superior Cu (II) adsorption capacity (18.5 mg/g) and fast adsorption speed. Abstract: Cork is light, porous, carbon-rich, and renewable, which leads to competitive advantages in the preparation of biochar, as compared to other biomass material. In this work, we propose to convert cork powder into cork-based biochar as Cu (II) adsorbent via slow pyrolysis, thereby providing a reliable and simple method for recycling cork industrial waste. The physicochemical properties of cork-based biochar prepared under different pyrolysis temperatures (450, 550, 650, and 750 °C) and pyrolysis time (0.5, 1.0, 1.5, and 2.0 h) were characterized by elemental analysis, FT-IR, XRD, N2 adsorption and SEM. The adsorption capacity of cork-based biochar on heavy metal ions was further evaluated by Cu ion adsorption testing. Results showed that the cork-based biochar produced under conditions of higher pyrolysis temperature and time, has higher aromaticity and lower polarity, larger specific surface area, and enhanced Cu ion adsorption capacity. The maximum specific surface area of cork-based biochar prepared at 750 °C for 0.5 h was 392.5 m 2 /g, which surpasses most other biochars reported in previous studies, which are beneficial to the application of wastewater management. The SEM image demonstrated that the biochar retains the special hollow polyhedral cell structure of raw material cork. Furthermore, a large number of pores formed on the cell wall after high temperature pyrolysis, and the cells are connected with each other through these open pores. Finally, cork-based biochar exhibits superior Cu ion adsorption capacity (18.5 mg/g) with a shorter equilibrium time (4 h), which gives it a competitive advantage to similar adsorbents.